Recommendations to address key recruitment challenges of Alzheimer's disease clinical trials. Issue 2 (10th August 2022) - Langbaum, Jessica B.; Zissimopoulos, Julie; Au, Rhoda; Bose, Niranjan; Edgar, Chris J.; Ehrenberg, Evan; Fillit, Howard; Hill, Carl V.; Hughes, Lynne; Irizarry, Michael; Kremen, Sarah; Lakdawalla, Darius; et al.
Abstract: Clinical trials for Alzheimer's disease (AD) are slower to enroll study participants, take longer to complete, and are more expensive than trials in most other therapeutic areas. The recruitment and retention of a large number of qualified, diverse volunteers to participate in clinical research studies remain among the key barriers to the successful completion of AD clinical trials. An advisory panel of experts from academia, patient‐advocacy organizations, philanthropy, non‐profit, government, and industry convened in 2020 to assess the critical challenges facing recruitment in Alzheimer's clinical trials and develop a set of recommendations to overcome them. This paper briefly reviews existing challenges in AD clinical research and discusses the feasibility and implications of the panel's recommendations for actionable and inclusive solutions to accelerate the development of novel therapies for AD.